2013
DOI: 10.1093/rheumatology/kes384
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution [18F]fluoride positron emission tomography of the distal interphalangeal joint in psoriatic arthritis--a bone-enthesis-nail complex

Abstract: This exploratory study suggested diffuse increased bone metabolism involving the entire DP, periosteum and entheses, especially in PsA. The subchondral bone and periosteum at the DP have large concentrations of enthesis attachments, including attachments from the nail, supporting the concept of an integrated nail and joint apparatus leading to a wide area of abnormal bone metabolism in PsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 21 publications
1
16
0
1
Order By: Relevance
“…Furthermore, these entheseal changes were found to be consistently identified when clinically evident nail disease was present. 7,22,27,28 These imaging studies not only sustained the now established notion that enthesopathy is the major feature of PsA, but also suggested that nail disease in psoriasis may be associated with subclinical entheseal disease.…”
Section: Entheses: the Anatomical Site Of Joint Inflammationmentioning
confidence: 54%
See 1 more Smart Citation
“…Furthermore, these entheseal changes were found to be consistently identified when clinically evident nail disease was present. 7,22,27,28 These imaging studies not only sustained the now established notion that enthesopathy is the major feature of PsA, but also suggested that nail disease in psoriasis may be associated with subclinical entheseal disease.…”
Section: Entheses: the Anatomical Site Of Joint Inflammationmentioning
confidence: 54%
“…5,6 Imaging studies have demonstrated the existence of considerable number of patients with psoriasis and undiagnosed PsA, a reflection of the presence of subclinical arthritic disease in clinically normal joints. 7,8 Persistent joint inflammation can lead to bone damage, and it is estimated that half of PsA patients develop irreversible joint lesions within the first few years of disease. 9,10 Therefore, PsA is a severe, erosive and deforming condition.…”
Section: Introductionmentioning
confidence: 99%
“…The system provided tomographic sampling, and attenuation and scatter correction of PET data employed the co-registered CT image. Recently, the feasibility of the quad-highdensity avalanche chamber nano-PET small-animal system, 31 the positron emission mammography Flex Solo II system 32,33 and the avalanche photodiode (APD)-based BrainPET system (Siemens Healthcare, Erlangen, Germany) 34 was demonstrated for wrist and hand arthritic imaging. These systems, however, did not have direct means for attenuation and scatter correction, and therefore radiotracer activity quantification is challenging.…”
Section: Fluorine-18 Fludeoxyglucose Uptake For the First Carpometacamentioning
confidence: 99%
“…According to recent studies, 18 F-FDG PET sensitively detects active inflammation in rheumatic diseases, including synovitis in RA [12][13][14][15][16][17][18]. In contrast, 18 F-NaF PET is an increasingly used molecular imaging modality in human skeletal disorders [19][20][21][22][23]. 18 F-NaF incorporates into the bone at the site of bone formation or remodeling; there, osteoblasts and osteoclasts are activated, and 18 F ions exchange the hydroxyl ions in bone crystal to form fluorapatite.…”
Section: Introductionmentioning
confidence: 99%